No-frills physics : a concise guide for algebra-based physics - McCluskey, Matthew D. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This textbook provides everything you need to get through a basic physics course. It guides students through all the essentials with a concise review of the concept, simple illustrations to demonstrate it, worked problems to showcase how to apply it, and a short quiz for self-testing.
Motion -- Vectors -- Forces -- Applying Newton's laws -- Circular motion and gravity -- Work and energy -- Rotational motion -- Momentum -- Oscillations and waves -- Fluids -- Thermodynamics -- Electric fields and forces -- Electric potential -- Electric circuits -- Magnetic fields and forces -- Electromagnetic induction -- Electromagnetic waves -- Optics -- Relativity -- Atoms and nuclei.
OCLC-licensed vendor bibliographic record.
Keywords: Physics -- Textbooks; SCIENCE / Energy; SCIENCE / Mechanics / General; SCIENCE / Physics / General